The changing levels of diffuse and specific support in South Africa amongst ANC supporters : a longitudinal study - Bosoga , Tebogo (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (Political Science))--University of Stellenbosch, 2009.